The substitution bias of the consumer price index - Petter Frenger (Statistics Norway, Research Department, 2006)
The paper uses elementary consumer theory to propose an inflation independent ratio definition of the substitution bias of the Laspeyres consumer price index, and derives an approximate substitution bias which depends on the size of the price change as measured by a norm in the Laspeyres plane and on the elasticity of substitution in the direction of the price change. This norm or distance measure can be interpreted as a price substitution index which yields useful information about the movements of relative prices. Norwegian CPI data are used to quantify these relationships.
Keywords: C43; D12; 330; consumer price index (CPI); substitution bias; elasticity of substitution.